Advantage of complex correction of vaginal microbiocenosis at an early reproductive age - E. V. Uvarova; Z. K. Batyrova (Медицинский совет, 2019)
Aim of the study: evaluation of the effectiveness of the integrated use of the Vagilac line of intimate hygiene products in young women with bacterial vaginosis (BV). Design of the study: prospective randomized intervention open study. Materials and methods: 45 menstruating young women diagnosed with «BW» at the age of 11-17 years, divided into 3 equal groups, were examined. In the 1st group adolescents received oral probiotic with Lactobacillus rhamnosus GR-1® and Lactobacillus reuteri RC-14® within 15 days, in the 2nd group within 30 days. Group 3 girls, along with probiotic, used liquid soap and Vagilac moisturising gel with lactic acid for intimate hygiene for 30 days. Diagnosis and control of the results were assessed taking into account complaints, vulvovaginoscopy, pH-metry, microscopy and molecular-genetic examination of vaginal microbiocenosis. Results: 1 month after the end of oral probiotic use, the share of Lactobacillus spp. in vaginal TBM in girls who received the probiotic within 15 days was 21.3%, 30 days 53.4%. The parallel use of liquid soap and Vagilac gel for intimate hygiene was manifested by the steady normalization of lactobacillus representation in the vagina. Conclusion: In the case of bacterial vaginosis in young girls, the most appropriate way to restore vaginal normocenosis was to use an oral probiotic with Lactobacillus rhamnosus GR-1® and Lactobacillus reuteri RC-14® for 30 days with the addition of liquid soap and Vagilac moisturising gel for intimate hygiene.